Extensive paraphyly in the typical owl family (Strigidae). (12th December 2019) - Salter, Jessie F; Oliveros, Carl H; Hosner, Peter A; Manthey, Joseph D; Robbins, Mark B; Moyle, Robert G; Brumfield, Robb T; Faircloth, Brant C
Abstract: The typical owl family (Strigidae) comprises 194 species in 28 genera, 14 of which are monotypic. Relationships within and among genera in the typical owls have been challenging to discern because mitochondrial data have produced equivocal results and because many monotypic genera have been omitted from previous molecular analyses. Here, we collected and analyzed DNA sequences of ultraconserved elements (UCEs) from 43 species of typical owls to produce concatenated and multispecies coalescent-based phylogenetic hypotheses for all but one genus in the typical owl family. Our results reveal extensive paraphyly of taxonomic groups across phylogenies inferred using different analytical approaches and suggest the genera Athene, Otus, Asio, Megascops, Bubo, and Strix are paraphyletic, whereas Ninox and Glaucidium are polyphyletic. Secondary analyses of protein-coding mitochondrial genes harvested from off-target sequencing reads and mitochondrial genomes downloaded from GenBank generally support the extent of paraphyly we observe, although some disagreements exist at higher taxonomic levels between our nuclear and mitochondrial phylogenetic hypotheses. Overall, our results demonstrate the importance of taxon sampling for understanding and describing evolutionary relationships in this group, as well as the need for additional sampling, study, and taxonomic revision of typical owl species. Additionally, our findings highlight how both divergence and convergence in morphological characters have obscured our understanding of the evolutionary history of typical owls, particularly those with insular distributions.